Iron improves the antiviral activity of NK cells - Schimmer, Simone; Sridhar, Vaasudevan; Satan, Zelal; Grebe, Anton; Saad, Mohamed; Wagner, Bernd; Kahlert, Nele; Werner, Tanja; Richter, Dana; Dittmer, Ulf; Sutter, Kathrin; Littwitz-Salomon, Elisabeth (Frontiers in Immunology, 2025)
Natural killer (NK) cells are innate immune cells that play a crucial role as a first line of defense against viral infections and tumor development. Iron is an essential nutrient for immune cells, but it can also pose biochemical risks such as the production of reactive oxygen species. The importance of iron for the NK cell function has gained increasing recognition. We have previously shown that NK cells require iron to efficiently eliminate virus-infected target cells; however, the impact of nutritional iron deficiency on NK cell function and the therapeutic benefits of iron supplementation remain unclear. Here, we demonstrate that diet-related low iron levels lead to increased retroviral loads due to functional NK cell impairment, while iron supplementation enhances NK cell proliferation, as well as their cytotoxic efficacy. Notably, iron-treated NK cells exhibited significant metabolic changes, including mitochondrial reorganization. Interestingly, although iron supplementation decreased the NK cell’s cytokine production, it significantly improved NK cell degranulation and the expression of cytotoxicity-associated proteins. These findings highlight the critical role of iron in maintaining NK cell immunity and suggest that iron supplementation may hold therapeutic potential for supporting the treatment of viral infections and immunodeficiency disorders.